Teaching Writing Comparison Contrast Essay by Using Venn Diagram to Second Year Sudents of English Department - Sinta Mustika; Aryuliva Adnan (Journal of English Language Teaching, 2019)
This paper aims to  explain how to teach writing comparison contrast essay by using Venn diagram. Comparison contrast essay is an essay that compares and contrasts two different topics focusing on the similarities and differences. The most common problem faced by students in writing comparison contrast essay is stating and organizing ideas to start writing. Considering this problem, teachers need to apply a teachnique in teaching and learning process. Venn diagram is a model that can be used to help students in stating and organizing the ideas in order to start writing. There are three stages in writing comparison contrast essay (Oshima and Hogue, 1999) : prewriting, planning (outlining), writing and revising. Venn diagram is used in the planning stages which help the students to state and organize ideas. In addition, this model also help the students to visualize the concept of comparison contrast essay.